Physical restraint use within long term care settings for older persons in Malta - Fenech, Maria Aurora (2016)
Purpose: To study this locally unexplored scenario and provide a platform of knowledge base and information on physical restraint use, securing relevant information of essence to the older person, care provider and policy makers within care homes.